In situ photocrosslinkable hyaluronic acid‐based surgical glue with tunable mechanical properties and high adhesive strength. Issue 4 (7th December 2018) - Chandrasekharan, Ajeesh; Seong, Keum‐Yong; Yim, Sang‐Gu; Kim, Sodam; Seo, Sungbaek; Yoon, Jinhwan; Yang, Seung Yun
ABSTRACT: Hyaluronic acid (HA), a naturally occurring linear polysaccharide, has been widely used as a key biomaterial in a range of cosmetic and therapeutic applications. Its excellent biocompatibility and bio‐functions related to tissue regeneration encourage the development of HA‐based hydrogels to expand its applications. This study details an in situ forming surgical glue based on photocrosslinkable HA, providing tunable mechanical properties and firm tissue adhesion under wet and dynamic conditions. Depending on the degree of photocrosslinkable methacrylate groups in HA polymer chains, the mechanical properties of hyaluronate methacrylate (HAMA) hydrogels prepared by UV photocrosslinking was improved. Ex vivo adhesion tests revealed that HAMA hydrogels exhibited 3‐fold higher shear adhesive strength compared to gelatin methacryloyl hydrogels and achieved firm adherence to the porcine skin tissue for several weeks. The high adhesive strength of HAMA hydrogels, under dry and wet conditions, suggests that it may have great promise as a tissue adhesive. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2019, 57, 522–530 Abstract : An in situ forming surgical glue based on photocrosslinkable hyaluronic acid, providing tunable mechanical properties and firm tissue adhesion under wet and dynamic conditions has been investigated. Ex vivo adhesion tests revealed that hyaluronate methacrylate (HAMA) hydrogels exhibited 3‐fold higher shear adhesive strength compared to gelatin methacryloyl hydrogels and achieved firm adherence to the porcine skin tissue for several weeks. These suggest that HAMA may have great promise as a tissue adhesive.